Diagnostic efficacy of C4d immunostaining in the detection of the humoral component of renal allograft rejection and therapeutic implications - Guduru Sree; Kuruvilla Sarah; Abraham Georgi; Mathew Milly; Saravanan S (Wolters Kluwer Medknow Publications, 2009)
Context: In the current scenario of renal transplantation, the role of immunological methods in the detection of C4d has emerged as a useful adjunct in the recognition of acute humoral rejection (AHR). Few reports of this nature are available from the Indian context although there are several from the Western literature. Aims: To study the humoral component of renal allograft rejection in patients presenting clinically with graft dysfunction by histopathological detection of polymorphs in the peritubular capillaries and the expression of C4d using immunological techniques, as well as the response of patients to appropriate antirejection therapy. Settings and Design: This study from a tertiary care center reemphasizes the importance of recognition of AHR as a cause of renal allograft dysfunction. Materials and Methods: Percutaneous renal biopsies were obtained from 40 postrenal transplant patients and evaluated for C4d using immunofluorescence and immunohistochemical methods. Statistical a0 nalysis used: SPSS software. Results: Positive expression of C4d was seen in a total of 19/40 cases (44.4%) indicating immunological evidence of AHR. Diffusely positive cases were treated with IV immunoglobulin therapy, plasmapheresis and Rituximab following which graft function was restored. Patients with minimal to focal positive expression of C4d responded well to pulse steroids and change in immunosuppressive therapy. Conclusions: C4d staining is a useful adjunct to routine histopathological methods in evaluating the humoral component of acute renal allograft dysfunction and helps in planning appropriate antirejection therapy with the goal of achieving long-term graft survival.